Carbon and Carbon Hybrid Materials as Anodes for Sodium‐Ion Batteries. Issue 10 (19th April 2018) - Zhong, Xiongwu; Wu, Ying; Zeng, Sifan; Yu, Yan
Abstract: Sodium‐ion batteries (SIBs) have attracted much attention for application in large‐scale grid energy storage owing to the abundance and low cost of sodium sources. However, low energy density and poor cycling life hinder practical application of SIBs. Recently, substantial efforts have been made to develop electrode materials to push forward large‐scale practical applications. Carbon materials can be directly used as anode materials, and they show excellent sodium storage performance. Additionally, designing and constructing carbon hybrid materials is an effective strategy to obtain high‐performance anodes for SIBs. In this review, we summarize recent research progress on carbon and carbon hybrid materials as anodes for SIBs. Nanostructural design to enhance the sodium storage performance of anode materials is discussed, and we offer some insight into the potential directions of and future high‐performance anode materials for SIBs. Abstract : Anodes for SIBs : Sodium‐ion batteries (SIBs) have attracted much attention for application in large‐scale grid energy storage owing to the abundance and low cost of sodium sources. In this review, we summarize recent research progress on carbon and carbon hybrid materials as anodes for SIBs.